SWITCHING BIOLOGICS IN PSORIASIS: CHALLENGES AND EXPERIENCE FROM A SMALL TERTIARY HEALTH-CARE CENTER - Bojic Djurovic, Milica; Bojic, Milos; Popovic, Ana; Golubovic, Mileta; Raznatovic Djurovic, Milena (Sanamed, 2024)
Objective: Psoriasis, a chronic inflammatory skin disease, significantly impacts patients’ quality of life. Over the last decade, therapeutic goals have aimed to complete skin clearance and restore normal patient activities, minimizing the disease’s impact on social, family, and work activities. Biologics have emerged as a promising solution to achieve better disease control without organ-specific side effects, helping meet these therapeutic goals. However, it was soon noticed that approximately 30% of patients do not sufficiently react to the therapy in the long term, and the need for switching biologics emerges. Findings: We present our experience with biologic switching over a specific period. Seventeen patients required a switch in biologic agents, with three undergoing a second switch. The cohort predominantly consisted of males (14 out of 17), with an average BMI of 29.81. The primary reasons for switching were secondary failure (loss of initial treatment efficacy), followed by primary failure. Adverse reactions were the least common cause, highlighting the satisfactory safety profile of biologics. One patient underwent dose escalation of secukinumab due to efficacy failure but ultimately ended up switching the biologic. Conclusion: Biologic agents approved for the treatment of psoriasis showed a favorable safety profile without compromising efficacy. The increasing demand for higher efficacy in psoriasis treatment aims to alleviate the disease’s multifaceted impact on patients. It is anticipated that biologic switching, primarily due to inadequate therapeutic response and less frequently due to adverse reactions, will become more prevalent in clinical practice. Literature and our clinical experience suggest that constitutional factors influence treatment success. As new agents and targets emerge, the established standards for biologic switching may require ongoing revision.